APPLICATION OF OUTDOOR STUDY TO IMPROVE INDEPENDENCE AND DRAWING CREATIVITY (Study of Children in Group B Paud Radiallahu Anh, Ujan Mas, Kepahiang District) - Prety Citra Pratesi; Nina Kurniah (UNIB Press, 2019)
This study aim to know the application of Outdoor Study to improve the independence and creativity of drawing for early childhood especially those aged 5-6 years. This research is a classroom action research consisting of 3 stages, which is planning, implementation and observation, and reflection. The research subjects were children aged 5-6 years in Radiallahu Anh PAUD, totalling 28 people. Data collection is done through observation. Data analysis using averages and t-test. The results showed that the application of Outdoor Study was able to increase children independence to 43% in 3 cycles and drawing creativity to 36% in 3 cycles